1962
DOI: 10.2136/sssaj1962.03615995002600050013x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Reaction Products from Phosphate Fertilizers in Soils

Abstract: Approximately 30 crystalline phosphate compounds, in addition to colloidal precipitates of variable composition, were identified as reaction products following the addition of various fertilizer solutions to soils and soil constitutents. The identifications were made by means of X‐ray, petrographic, and chemical analyses. The findings help to clarify the mechanism of phosphate reactions in soils, which includes the dissolution of fertilizer and soil constituents and the precipitation of new products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0
3

Year Published

1966
1966
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(65 citation statements)
references
References 0 publications
5
57
0
3
Order By: Relevance
“…2A). As reported by Lindsay et al (1962), the pH of a saturated solution of KH 2 PO 4 was 4.0. This implies that the salt applied was thoroughly dissolved and H + produced was transported down to the bottom without interaction.…”
Section: The Ph Profiles Of Mixturesupporting
confidence: 55%
See 1 more Smart Citation
“…2A). As reported by Lindsay et al (1962), the pH of a saturated solution of KH 2 PO 4 was 4.0. This implies that the salt applied was thoroughly dissolved and H + produced was transported down to the bottom without interaction.…”
Section: The Ph Profiles Of Mixturesupporting
confidence: 55%
“…Lindsay et al (1962) identified approximately 30 crystalline phosphate compounds in addition to colloidal precipitates of variable composition as reaction products of various phosphate fertilizers. Hsu and Rennie (1962) reported a basic Al(OH) 2 H 2 PO 4 was formed by the addition of Al 3+ -resin into NaH 2 PO 4 solution.…”
mentioning
confidence: 99%
“…LÍndsay and Stephenson (17) f ound that DCP Ð f ormed not only at the f ertiliser placement CaHPO (16) found DCPD precipitates remaining in filtrates for two months when soils were treated wíth saturated phosphate solutions. Larson g.I .e,1.…”
mentioning
confidence: 99%
“…The higher levels of extractable P with (APP) could have resulted from the lower uptake of P from this treatment and / or the formation of fertilizer reaction products that were more soluble in the double-acid extractant. Although the fertilizer reaction products of (OP) and polyphosphate in soils have been studied (Savant and Racz, 1973;Lindsay et al, 1962;Philen andLehr, 1967, Fatma et a.l, 2013), no information is available concerning their solubilities in the double-acid extracting solution.…”
Section: The Soil Datamentioning
confidence: 99%